2021
DOI: 10.1126/scitranslmed.abd2223
|View full text |Cite
|
Sign up to set email alerts
|

IgA dominates the early neutralizing antibody response to SARS-CoV-2

Abstract: Humoral immune responses are typically characterized by primary IgM antibody responses followed by secondary antibody responses associated with immune memory and composed of IgG, IgA, and IgE. Here, we measured acute humoral responses to SARS-CoV-2, including the frequency of antibody-secreting cells and the presence of SARS-CoV-2–specific neutralizing antibodies in the serum, saliva, and bronchoalveolar fluid of 159 patients with COVID-19. Early SARS-CoV-2–specific humoral responses were dominated by IgA anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

72
831
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 932 publications
(967 citation statements)
references
References 50 publications
72
831
3
1
Order By: Relevance
“…The copyright holder for this preprint this version posted January 25, 2021. ; https://doi.org/10.1101/2021.01.25.428097 doi: bioRxiv preprint 6 neutralization activity in their plasma at the last time point (Figure 2A). Since the depletion of IgM from plasma has been associated with loss of viral neutralization capacity (28,29) and IgA has also been shown to dominate the early neutralizing response (30,31), the sharp decline in neutralization activity seen in this study is corroborated by the striking decrease in anti-Spike and anti-RBD IgM and IgA levels (Figure 1B, D, F, H; Figure S1A, B). Fc-mediated effector functions of antibodies can contribute to the efficacy of immune response against SARS-CoV-2.…”
Section: Neutralizing and Fc-effector Activities Of Antibodies Presensupporting
confidence: 67%
“…The copyright holder for this preprint this version posted January 25, 2021. ; https://doi.org/10.1101/2021.01.25.428097 doi: bioRxiv preprint 6 neutralization activity in their plasma at the last time point (Figure 2A). Since the depletion of IgM from plasma has been associated with loss of viral neutralization capacity (28,29) and IgA has also been shown to dominate the early neutralizing response (30,31), the sharp decline in neutralization activity seen in this study is corroborated by the striking decrease in anti-Spike and anti-RBD IgM and IgA levels (Figure 1B, D, F, H; Figure S1A, B). Fc-mediated effector functions of antibodies can contribute to the efficacy of immune response against SARS-CoV-2.…”
Section: Neutralizing and Fc-effector Activities Of Antibodies Presensupporting
confidence: 67%
“…However, it is not known which type of antibody predominantly plays a role in neutralization because the CRNT result reflects the comprehensive action of a variety of antibodies. In a recent study on COVID-19, Sterlin et al [8] suggested that neutralizing capacity rapidly increased and plateaued by day 10 post-symptom onset, which is All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, results of the cPass assay are best correlated with those of a laboratory-developed indirect anti-RBD ELISA detecting IgG, both at a single timepoint (Table 2, Figure 3) and across time among paired specimens form the same individual collected at a known interval from symptoms onset (Figure 4). The fact that results of cPass and anti-RBD IgG remained stable between 6 and 10 weeks post-symptom onset, while optical densities decreased significantly over the same timeframe for anti-RBD IgM and IgA ELISA is potentially concerning given recent work suggesting a major role of IgM and IgA in the neutralizing activity of convalescent plasma against SARS-CoV-2 (25-28). The observed trend toward lower specificity at later timepoints among convalescent plasma donors with longitudinal follow-up (i.e.…”
Section: Discussionmentioning
confidence: 98%